2009
DOI: 10.1002/stem.27
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Depletion of Human Skin-Derived Progenitor Cells

Abstract: A major unanswered question in autologous cell therapy is the appropriate timing for cell isolation. Many of the putative target diseases arise with old age and previous evidence, mainly from animal models, suggests that the stem/progenitor cell pool decreases steadily with age. Studies with human cells have been generally hampered to date by poor sample availability. In recent years, several laboratories have reported on the existence, both in rodents and humans, of skin-derived precursor (SKP) cells with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 43 publications
(81 reference statements)
2
73
0
1
Order By: Relevance
“…In contrast to reports on the negative effect of ageing on adult SC growth and functionality [18][19][20][21][22]57], the growth during the first 10 population doublings, the fraction of cells expressing Nanog and Oct4, the level of transcription of these factors, and the in vitro differentiation capacity of hOMSC were not affected by the donor age, thus, providing a biological explanation for the negligible ageing effect on wound healing in the elderly oral mucosa [25]. However, the increase in the doubling time at higher population doublings in elderly derived cultures suggests that mechanisms active in preserving telomeres length in EhOMSC is less effective than in YhOMSC.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In contrast to reports on the negative effect of ageing on adult SC growth and functionality [18][19][20][21][22]57], the growth during the first 10 population doublings, the fraction of cells expressing Nanog and Oct4, the level of transcription of these factors, and the in vitro differentiation capacity of hOMSC were not affected by the donor age, thus, providing a biological explanation for the negligible ageing effect on wound healing in the elderly oral mucosa [25]. However, the increase in the doubling time at higher population doublings in elderly derived cultures suggests that mechanisms active in preserving telomeres length in EhOMSC is less effective than in YhOMSC.…”
Section: Discussionmentioning
confidence: 74%
“…hOMSC are endowed with a relatively high, telomeraseindependent self-renewing capacity and cloning efficiency compared with MSC derived from other tissue [19,22]. hOMSC produce and secrete FGF-2, EGF, VEGF, and NGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodent SKPs are capable of repairing damaged muscles, bones, as well as the nervous system [3][4][5]. Although human SKPs (hSKPs) can be isolated with similar protocols, their longterm expansion in vitro is defective [6,7]. We previously demonstrated that foreskin-derived adult hSKPs senesced quickly in vitro, which could be partially alleviated by enhancing PI3K-Akt pathway activity or culturing hSKPs with micro-environment-mimicking three-dimensional hydrogel scaffolds [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These neural crest related ASC can also be isolated from skin of the abdomen [30], breast [30], arm [31], face [32], and scalp [33] mostly upon aesthetic interventions. These cells have a high self-renewal and high multipotent differentiation capacity.…”
Section: Introductionmentioning
confidence: 99%